2005
DOI: 10.1158/1078-0432.ccr-05-1157
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Screening of Genomic Alterations and Their Clinicopathologic Implications in Non–Small Cell Lung Cancers

Abstract: Purpose: Although many genomic alterations have been observed in lung cancer, their clinicopathologic significance has not been thoroughly investigated. This study screened the genomic aberrations across the whole genome of non^small cell lung cancer cells with high-resolution and investigated their clinicopathologic implications. Experimental Design: One-megabase resolution array comparative genomic hybridization was applied to 29 squamous cell carcinomas and 21adenocarcinomas of the lung. Tumor and normal ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 27 publications
8
47
0
Order By: Relevance
“…This agrees with previous reports in which SFTPC gene is located in chromosome 8p21.3, and deletion of the 8p21 occurs later in the process of lung tumorigenesis and is associated with the metastatic phenotype of the disease (24). Thus, the detection of SFTPC deletions might not be a biomarker in sputum for lung cancer diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…This agrees with previous reports in which SFTPC gene is located in chromosome 8p21.3, and deletion of the 8p21 occurs later in the process of lung tumorigenesis and is associated with the metastatic phenotype of the disease (24). Thus, the detection of SFTPC deletions might not be a biomarker in sputum for lung cancer diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…The PIK3CA gene, located at 3q26.3 locus, has been reported to be amplified in squamous cell carcinoma (4, 28) and, as expected, was not identified as a recurrent CNA in our series. In a similar vein, we observed recurrent gains of 6p and recurrent losses of 13, both of which have been shown to occur in lung adenocarcinomas (5,26).…”
Section: Resultssupporting
confidence: 76%
“…Regions exhibiting copy number alterations (CNA) can affect the expression of cislocalized tumor suppressor genes and oncogenes. However, only few reports have suggested a potential relationship between recurrent CNAs and NSCLC patient prognosis (4,5). In addition, the architecture of CNAs is often complex (multiple ''subalterations '') and not all genes within a CNA region will necessarily show altered gene expression (''copy number-driven'' expression; refs.…”
Section: Introductionmentioning
confidence: 99%
“…STK15 is a serine/threonine protein kinase modulating G 2 -M cell cycle progression through its regulation of mitotic spindle formation and centrosome duplication (42). Dysfunction of STK15 might result in aberrant chromosome segregation, a potential early event of lung carcinogenesis (42,43). Numerous reports have shown that p53 is one of the most frequently mutated genes in smoking-associated lung cancers (44,45).…”
Section: Discussionmentioning
confidence: 99%